Gestural Interaction for Accessibility of Web Videos - A Case Study Analysis with Blind and Visually Impaired Users - Funes, Marcio Maestrelo; Fortes, Renata P. M.; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
This article describes a gestural interaction case study conducted with 36 blind and visually impaired users. Task-based user evaluations were undertaken on three phases to answer the question: Can gesture interactions improve the experience of blind or visually impaired users for Web videos accessibility? After the study case analysis, 97% of the users would use a gestural interface and 92% preferred gesture interaction compared to the usual interaction. To obtain the conclusions, the variables were analyzed by comparisons of percentages and chi-square test.